ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PERTUMBUHAN EKONOMI DAN KEMISKINAN KABUPATEN/KOTA DI SUMATERA UTARA - Kawi, Rebecca Dian Aprilia; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 4 (2022): Vol. 11 No. 4, April 2022 [1215-1619], 2022)
Economic growth important benchmarks in success economic development. Economic growth in North Sumatra very good picture compared to national economic growth although there are still gaps between regions. The research are to analyze (1) direct influence of unemployment rate and education level on economic growth in districts/cities in North Sumatra Province; (2) direct influence of the unemployment rate, education level and economic growth on the poverty rate in districts/cities in North Sumatra Province; (3) indirect effect of unemployment rate and education level on poverty level through economic growth in regencies/cities in North Sumatra Province. The observations 99 points with path analysis techniques. The results are (1)Unemployment Rate hasn’t significant positive effect, but Education Level has a significant positive effect on economic growth; (2) Unemployment rate has no significant positive effect, but unemployment rate and economic growth have a significant negative effect on the poverty rate of districts/cities in North Sumatra Province; (3) The unemployment rate does not indirectly affect poverty through economic growth, but the level of education partially indirectly affects the poverty rate through the economic growth of districts/cities in North Sumatra Province. Keywords: unemployment rate, education level, economic growth, poverty rate